the Making of Teaching Profession as a First Choice - Sara Jane Cruz; Julius Meneses; Nilmar Moreno (Diversitas Journal, 2023)
In the global educational scene, the teaching profession has long been hailed as the noblest profession. It is through educators; that the citizenry is currently imbued with skills and knowledge that they need to maximize their capacities to their full potential. Thus, the researchers saw that it is pivotal to know the perception of the pre-service teachers on the teaching profession as a first choice, to provide baseline data that can unveil factors that influence the making and unmaking of the teaching profession. Using the descriptive research method, the data from a survey conducted among the 1st and 2nd-year students at the College of Education was gathered and interpreted. Subsequent to the t-test and Pearson correlation computation, the study uncovered that there is no significant difference in the perception of the 1st year respondents against the 2nd year respondents. Likewise, there is a moderately positive correlation in the respondents’ perception of teaching vis-à-vis teaching as a first choice and experience with their teachers.